1979
DOI: 10.1037/0278-7393.5.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Temporal coding in verbal information processing.

Abstract: Two experiments were conducted with a directed-forgetting paradigm to evaluate the degree of temporal information carried by the to-be-remembered (TBR) and the to-be-forgotten (TBF) items. The first experiment employed a serial position judgment task, and the second employed a pairwise comparison task under either primacy-or recency-judgment instructions. Both experiments showed that little temporal information was evidenced in the TBF items, whereas temporal'coding seemed to be "automatic" for the TBR items. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 25 publications
1
55
0
1
Order By: Relevance
“…Moreover, there is some evidence against this rehearsal hypothesis. For example, several studies have demonstrated that people extract positional information even under incidental learning (e.g., Hintzman, Block, & Summers, 1973;Nairne, 1992;Toglia & Kimble, 1976), although perhaps not as well as under intentionallearning (Tzeng, Lee, & Wetzel, 1979). Also, in a condition in which participants rehearsed lists overtly during the retention interval, Estes (1991) showed that the majority of items that did not occur in the rehearsal protocol could still occur at or near the correct position in recall.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is some evidence against this rehearsal hypothesis. For example, several studies have demonstrated that people extract positional information even under incidental learning (e.g., Hintzman, Block, & Summers, 1973;Nairne, 1992;Toglia & Kimble, 1976), although perhaps not as well as under intentionallearning (Tzeng, Lee, & Wetzel, 1979). Also, in a condition in which participants rehearsed lists overtly during the retention interval, Estes (1991) showed that the majority of items that did not occur in the rehearsal protocol could still occur at or near the correct position in recall.…”
Section: Discussionmentioning
confidence: 99%
“…Age of the trace probably provides useful time information for shorter delays than those tested here. A number of the verballeaming studies show "recency effects" for accuracy of time judgments when recall is within a few minutes of the end of the list (e.g., Hintzman et al, 1973;Tzeng, 1976), but these effects are typically absent for longer delays (e.g., Hintzman et aI., 1973;Tzeng et al, 1979). The apparent paradox that more recent events are more accurately dated in the long-term memory studies, including this one, could be attributed to forgetting contextual associates of the events from which time of occurrence can be inferred.…”
Section: Discussionmentioning
confidence: 99%
“…First, free recall performance depends jointly on encoding information about the individual items in the list (termed item-specific processing) and information about the relations among the list items (termed relational processing; Einstein & Hunt, 1980;Hunt & McDaniel, 1993;Mandler, 1969). Second, for lists of unrelated items (such as those used in the orthographic distinctiveness literature), the primary relational information available is the serial order in which the list items are presented (e.g., Toglia & Kimble, 1976;Tzeng, Lee, & Wetzel, 1979), and such information is relied upon to guide free recall (Burns, 1996;Postman, 1972).…”
Section: The Item-order Accountmentioning
confidence: 99%